Issue of gharar in the housing statutory standard sale and purchase agreement in Malaysia - Md Dahlan, Nuarrual Hilal (2012)
It is well entrenched in the Housing Development (Control and Licensing;) Act 1966 (Act 118) and its regulations that all purchases of house which are subject to this act, must use the prescribed housing statutory standard sale and purchase agreements as contained in Schedules G, H, I and J ('the said agreements 7. These schedules provide the terms and conditions of the sale, including the rights and liabilities of the vendor developers and the purchasers. Nonetheless, according to a research, the said agreements are not fully in compliance with Islamic Law.This is premised on the ground that the terms and conditions in said agreements are insufficient to the meet the problems of abandoned housing projects and other housing troubles. Due to this inadequacy, the said agreements, particularly Schedules G and H, contain gharar al-fahish (exorbitant gharar) elements which could null& the validity of the said agreements according to Islamic Law. This paper is to elaborate and discuss the issue of gharar in the said agreements.This paper also is a result of a completed research funded by UUM University Research Grant. The objective of this paper is to re-visit the legality of the said agreements which are considered null and void as they contained gharar al-fahish elements.The re-visit is important as there are new housing development legal and nonlegal approaches and policies introduced by the government lately to overcome the problems of abandoned housing projects and other housing problems.The question is: Whether these new approaches can eliminate the elements of gharar al-fahish as purported inherent in the said agreements in protecting the interests and rights of the purchasers in abandoned housing projects? The fruit of this paper is a result from a research that used qualitative and legal research methodology.The finding of this paper is that even though with the introduction of the new approaches of the government in dealing abandoned housing projects, these approaches may not fully able to eliminate the elements of gharar al-fahish in the said agreements to the detriment of the purchasers in abandoned housing projects. Due to this, the purchasers are still the fallen preys to the unscrupulous abandoned housing developers. This paper also provides certain suggestions to settle the problems plaguing the said agreements for the betterment of the housing industry in Malaysia.